Pengaruh Citra Merek, Label Halal, Social Media Influencer dan Kualitas Produk terhadap Customer Loyality - Setyarini, Riska Ayu; Alfalisyado, Alfalisyado; Astuti, Herni Justiana; Fauziridwan, Meydy (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
The purpose of this study was to analyze the influence of brand image, halal label, social media influencers, and product quality on customer loyalty of Somethinc products in the Banyumas region. The method used was quantitative, with a sample of 100 respondents selected through a purposive sampling technique. Data were collected through a structured questionnaire and analyzed using multiple linear regression. The results showed that simultaneously and partially there was a significant influence between the variables of brand image, product quality, and social media influencers on customer loyalty of Somethinc products in the Banyumas region.